2019
DOI: 10.1111/mmi.14352
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma reesei XYR1 recruits SWI/SNF to facilitate cellulase gene expression

Abstract: Summary Cellulase gene expression in Trichoderma reesei is highly responsive to environmental cues and is under stringent regulation by multiple transcription factors. XYR1 (Xylanase regulator 1) has been identified as the most important transcriptional activator of cellulase/hemicellulase gene expression although the precise transactivating mechanism remains largely elusive. Here we show that the activation domain of XYR1 interacts with the T. reesei homolog of the TrSNF12 subunit of SWI/SNF complex. Deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…The missing 140 C-terminal amino acids of Xyr1 abolished cellulase production (Lichius et al, 2015). Recent studies have revealed the transcription factor Xyr1 AD could recruit SWI/SNF to remodel nucleosomes positioned in cellulase gene promoters for activating their transcription (Cao et al, 2019), suggesting the important role of this AD in regulation of cellulase gene expression. Therefore, we speculated that Xyr1 AD may function better than Gal4 AD to regulate cellulase gene expression in T. reesei.…”
Section: Discussionmentioning
confidence: 99%
“…The missing 140 C-terminal amino acids of Xyr1 abolished cellulase production (Lichius et al, 2015). Recent studies have revealed the transcription factor Xyr1 AD could recruit SWI/SNF to remodel nucleosomes positioned in cellulase gene promoters for activating their transcription (Cao et al, 2019), suggesting the important role of this AD in regulation of cellulase gene expression. Therefore, we speculated that Xyr1 AD may function better than Gal4 AD to regulate cellulase gene expression in T. reesei.…”
Section: Discussionmentioning
confidence: 99%
“…For construction of the strain expressing a protein A-tagged TrGAL11, the trp C terminator was amplified from pMDP tcu1 -T trpC [ 37 ], digested with Hin dIII/ Asc I, and then ligated into pUC19- pyr4 [ 55 ] to obtain pUC19- pyr4 -T trpC . The protein A tag encoding sequence was amplified from the pMDP tcu1 proA- Trswi1 plasmid [ 56 ], digested with Not I/ Pme I, and subsequently ligated into the pUC19- pyr4 -T trpC plasmid to obtain the knock-in plasmid pUC19- pyr4 -proA. Finally, a 2 kb fragment upstream from the stop codon of the Trgal11 gene and a 2.3 kb fragment downstream from TGA were amplified from QM9414 genomic DNA, digested with Hin dIII/ Not I and Xba I/ Spe I respectively, and then ligated into pUC19- pyr4 -proA to fuse the Trgal11 with protein A coding sequence to obtain the pUC19- Trgal11 -proA-KI plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…For the expression of TrGAL11 KIX (amino acids 1~134) and XYR1 AD in E. coli, the DNA fragment coding for TrGAL11 KIX was amplified from the T. reesei cDNA and was inserted into the pET28a (+) expression vector after digestion with NdeI and NotI to obtain the pET28a-TrGAL11 KIX plasmid. Similarly, the XYR1 AD (amino acids 767~860) was amplified from the pGBKT7-XYR1 AD plasmid [56] and ligated into the pGEX4T-1 expression vector after digestion with NotI and BamHI. To purify the GST-XYR1 AD 767-860 and TrGAL11 KIX-His, the indicated expression constructs were transformed into CaCl 2 -treated competent E. coli BL21 (DE3) cells.…”
Section: Protein Production In E Coli and Gst Pull Down Assaysmentioning
confidence: 99%
“…However, the transcript of rxe1 homolog (Th_61248) in T. harzianum LZ117 was dramatically decreased, thus the regulatory relationship between Rxe1 and Xyr1 in T. harzianum remains unclear. It was also revealed that Xyr1 recruits SWI/SNF complex through direct interactions with TrSNF12 to remodel chromatin at cellulase gene promoters, thereby activating cellulase gene expression in T. reesei (Cao et al, 2019) but no significant change for the transcription of Trsnf12 homolog (Th_101097) in T. harzianum LZ117 was found as compared to the control strain. The Velvet family protein Ve1 (Liu et al, 2015) in T. reesei plays an important role in the regulation of cellulase expression, while transcriptional level of its homologous gene veA (Th_95531) in T. harzianum LZ117 has not changed significantly.…”
Section: Changed Genes That Encode Regulators and Major Transportersmentioning
confidence: 98%